ADAPTING CHARACTER SPEECH IN THE DUBBING OF ANIMATED FILMS - Yuldosh Abdurakhmonov (International Journal of Literature and Language Studies, 2026)
This article examines the issues involved in adapting character speech to the target language in the process of dubbing animated films. The aim of the study is to identify and classify the translation strategies employed when transferring the individual speech features of animated characters (idiolect, register, accent and voice timbre) from one language into another. The study applies a comparative-descriptive method and audiovisual analysis; the unit of analysis comprises segments of a character’s spoken speech together with their corresponding scene frames. The results show that adapting character speech in dubbing is constrained not only by semantic equivalence but also by the requirements of three types of synchrony — phonetic, kinetic and isochrony. In transferring humour, wordplay, accent and cultural references, the translator frequently abandons equivalence and resorts to functional adaptation. The conclusions of the article are of both theoretical and practical significance for the practice of dubbing animated products into Uzbek.